The epistemology and morality of human kinds - Godman, Marion (Routledge focus on philosophy, 2021)
"Natural kinds is a widely used and pivotal concept in philosophy, being the idea that the classifications and taxonomies employed by science correspond to the real kinds in nature. Natural kinds are often opposed to the idea of kinds in the social sciences, which are characterised by changing norms and practices and resist scientific reduction. Yet human beings are also a subject of scientific study. Does this mean they have a corresponding kind of their own? If there is such a thing as human kinds, do they have essences? In The Epistemology and Morality of Human Kinds Marion Godman defends the idea of human kinds. She first examines the formation and nature of human kinds, considering the arguments of key philosophers whose work bears upon human kinds, such as Ian Hacking, John Searle, Richard Boyd and Ruth Millikan. Using the examples of gender, Buddhism and mental disorder she then argues that human kinds are a result of ongoing historical reproduction, either cultural or consisting of a blend of cultural and biological reproducibility. Her novel argument shifts the focus away from the reductionism characteristic of research about human kinds. Instead, she argues that they are 'multiply projectible' and deserving of scientific study not in spite of, but because of their role in explaining our identity, culture and social membership"--